Utilization of Gamma Co-60 Radiation for Chili Plant (Capsicum annuum L.) Breeding by Using a Physical Mutagen Method - Purmita Sari, Ni Made; Sutapa, Gusti Ngurah; Gunawan, A.A. Ngurah (BULETIN FISIKA, 2020)
Chili is one type of vegetable that has many benefits and is favored in Indonesia and aboard. The benefits of chili are used as a kitchen spice and are used in the health sector as a mixture of herbal medicines and even as anti-cancer. Based on data from the Ministry of Agriculture of the Republic of Indonesia, chili productivity per plant is still relatively low (0.20-0.33 kg/tree or 6.84 tons/ha, so there needs an effort for improvement of productivity. Increased chili productivity can be done by plant breeding. In this study has been carried out Co-60 gamma radiation in plant breeding of chili (Capsicum annuum L. ) by physical mutagen method. The chili used is red chili (hot chili F1). The purpose of this study is to find out the right Co-60 radiation dose for chili plant breeding. The gamma radiation dose used is 0 Gy as a control, 50, 75, 100, 125 and 150 Gy. The results showed that the right radiation dose for chili plant breeding was 75 Gy.